A microbiological survey on tomatoes (Lycopersicon esculentum Mill) marketed in Rio de Janeiro, Brazil - Ana Lucia Penteado; Maria Fernanda Demonte Penteado Moretzsohn de Castro; Ricardo Antônio Almeida Pazianotto (Fundação Oswaldo Cruz (FIOCRUZ), 2016)
Fresh produce can be a possible source of microbiological contamination. In the past 20 years, several salmonellosis outbreaks due to the consumption of tomato have been reported, mainly in the USA. Organic raw vegetables pose a risk for the transmission of foodborne pathogens since they are often cultivated using manure as a fertilizer. The aim of this study was to conduct a survey of the presence of Salmonella spp, total coliforms and Escherichia coli on the surface of tomatoes from two different production systems. A total of 262 samples of organic and conventional tomatoes were collected from supermarkets and open street markets in the city of Rio de Janeiro, Brazil and analyzed for these microorganisms. To increase the probability of detecting Salmonella spp, we used two different detection methods: the traditional method from the Bacteriological Analytical Manual-Food and Drug Administration (BAM-FDA) and the Mini-Vidas-SLM-bioMÃ©rieux. Total coliforms were detected in the range of 1 to 4 log10 CFU/g, E. coli was found in only three samples (2 conventional and 1 organic) and Salmonella was absent in all of the analyzed samples. The results demonstrate that all of the samples were in agreement with the Brazilian legislation for Salmonella spp.Â